FAIM Is Regulated by MiR-206, MiR-1-3p and MiR-133b - Coccia, Elena (Front Cell Dev Biol, 2020)
Apoptosis plays an important role during development, control of tissue homeostasis and in pathological contexts. Apoptosis is executed mainly through the intrinsic pathway or the death receptor pathway, i.e., extrinsic pathway. These processes are tightly controlled by positive and negative regulators that dictate pro- or anti-apoptotic death receptor signaling. One of these regulators is the Fas Apoptotic Inhibitory Molecule (FAIM). This death receptor antagonist has two main isoforms, FAIM-S (short) which is the ubiquitously expressed, and a longer isoform, FAIM-L (long), which is mainly expressed in the nervous system. Despite its role as a death receptor antagonist, FAIM also participates in cell death-independent processes such as nerve growth factor-induced neuritogenesis or synaptic transmission. Moreover, FAIM isoforms have been implicated in blocking the formation of protein aggregates under stress conditions or de-regulated in certain pathologies such as Alzheimer’s and Parkinson’s diseases. Despite the role of FAIM in physiological and pathological processes, little is known about the molecular mechanisms involved in the regulation of its expression. Here, we seek to investigate the post-transcriptional regulation of FAIM isoforms by microRNAs (miRNAs). We found that miR-206, miR-1-3p, and miR-133b are direct regulators of FAIM expression. These findings provide new insights into the regulation of FAIM and may provide new opportunities for therapeutic intervention in diseases in which the expression of FAIM is altered.